FAMILY PHORIDAE - Ament, Danilo César; Brown, Brian V. (Zootaxa, 2016)
The Phoridae recorded from Colombia are catalogued, totaling 226 species distributed in 19 genera and three subfamilies. For each species, distribution, hierarchic position and cited references are presented.